A thermally conductive insulating material and its preparation method and application

By wrapping dopamine hydrochloride and perfluoroylsilane on the diamond particles, F-ND powder was prepared and added to the epoxy resin, the problem of diamond particles precipitation on the epoxy resin was solved, and the thermal conductivity and insulation properties were significantly improved.

CN118515953BActive Publication Date: 2025-03-07HARBIN UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410782527.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-18
Publication Date
2025-03-07
Estimated Expiration
2044-06-18

AI Technical Summary

Technical Problem

Existing diamond particles are prone to unilateral precipitation in epoxy resin, resulting in deterioration of thermal conductivity and insulation properties of thermally conductive packaging insulation materials.

Method used

The diamond powder is encapsulated by dopamine hydrochloride and polymerized with the dopamine chain on the diamond surface by the polymerization of the perfluorooctyltrimethoxysilane to obtain the perfluoro-silane-encapsulated fluorinated diamond powder F-ND, which is added to the epoxy resin matrix as a fill phase.

Benefits of technology

The thermal conductivity of epoxy resin composite materials is improved, the impact of single-sided settlement is reduced, the thermal conductivity and insulation performance is improved, and the preparation process is simplified, with low cost and high repeatability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118515953B_ABST
    Figure CN118515953B_ABST
Patent Text Reader

Abstract

The present invention discloses a thermally conductive insulating material and a preparation method and application thereof, and belongs to the technical field of thermally conductive packaging insulating composite materials and their preparation. The present invention solves the problems of unilateral precipitation and uneven dispersion caused by adding existing diamond particles to epoxy resin, which causes the thermal conductivity and insulation performance of thermally conductive packaging insulating materials to deteriorate. The present invention first uses diamond powder wrapped with dopamine hydrochloride, and then obtains fluorinated diamond powder wrapped with perfluorosilane by polymerization reaction between tridecafluorooctyltrimethoxysilane and dopamine chains on the surface of diamond, and then adds it as a filling phase to the epoxy resin matrix, thereby improving the thermal conductivity of the epoxy resin composite material, which is expected to be used as a new thermally conductive packaging insulating material for power semiconductor electronic devices. In addition, the preparation process of the epoxy resin composite material provided by the present invention has low cost, is easy to implement, has good environmental protection, and the operation of the required instruments is simple and safe.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a heat-conducting insulating material and a preparation method and application thereof, and in particular to a preparation method and application of a diamond surface-grafted epoxy resin-based heat-conducting insulating material, belonging to the technical field of heat-conducting packaging insulating composite materials and preparation thereof. Background Art

[0002] Power semiconductor electronic devices are developing towards high power density, high operating frequency and small size, which puts higher requirements on the electrical / thermal performance of their packaging insulation materials. If the heat generated by the power consumption of electronic devices continues to accumulate, its service performance and life will be significantly reduced. Therefore, the development of packaging insulation materials with high thermal conductivity and excellent dielectric properties is of great significance to improving the working characteristics of power electronic devices.

[0003] For epoxy resin-based potting materials commonly used in power semiconductor electronic devices, epoxy resin has good electrical insulation properties, but its intrinsic thermal conductivity is only 0.2W / m·K, which greatly limits the heat dissipation capacity of electronic devices. The common method in industrial production is to add nano-ceramic fillers such as boron nitride (BN), aluminum oxide (Al2O3), and aluminum nitride (AlN) to epoxy resin to improve the thermal conductivity of the potting material. In actual applications, due to the density of BN, Al2O3, and AlN (2.29g / cm 3 , 3.5g / cm 3 and 3.25g / cm 3 ) are greater than the common epoxy resin density (1.2g / cm 3 ), during the curing process, due to the density difference between the filler and the matrix, the filler often settles on one side in the matrix, which greatly affects the construction of the thermal conductive path of the filler in the epoxy resin matrix. Therefore, the filler mass fraction of the common epoxy resin potting glue containing thermal conductive fillers on the market is usually above 40%. The influence of unilateral sedimentation on thermal conductivity is reduced by increasing the filler content.

[0004] The thermal conductivity of diamond (ND) is as high as 2000W / m·K, which is much higher than the thermal conductivity of ceramic materials such as BN, Al2O3, and AlN (300W / m·K, 40W / m·K, and 200W / m·K, respectively). However, when it is added to epoxy resin as a carbon-based thermal conductive filler, the effect is not as good as that of BN and other materials. The reason is that the density of ND is as high as 3.52g / cm 3 And because of its more stable crystal structure, it is more susceptible to unilateral sedimentation due to density differences during the solidification process. Summary of the invention

[0005] The present invention aims to solve the problems of deterioration of thermal conductivity and insulation performance of thermal conductive packaging insulation materials caused by unilateral precipitation and uneven dispersion caused by adding existing diamond particles into epoxy resin, and provides a thermal conductive insulation material and a preparation method and application thereof.

[0006] The technical solution of the present invention:

[0007] One of the purposes of the present invention is to provide a method for preparing a thermally conductive insulating material, the method specifically comprising the following steps:

[0008] S1, adding PDA and ND to a tris(hydroxymethyl)aminomethane solution, stirring to obtain a suspension, then centrifuging, discarding the supernatant, washing the obtained precipitate with deionized water to obtain a neutral suspension, and freeze-drying the neutral suspension to obtain PDA-coated ND powder, named PDA-ND;

[0009] S2, adding the PDA-ND obtained in S1 to acetone, stirring evenly, adding tridecafluorooctyltrimethoxysilane to obtain a suspension, then centrifuging, discarding the supernatant, washing the obtained precipitate with ethanol and deionized water in sequence to prepare a suspension, freeze-drying the suspension to obtain tridecafluorooctyltrimethoxysilane-modified ND powder, named F-ND;

[0010] S3, mixing the F-ND obtained in S2, a curing agent and an epoxy resin, heating and stirring, and hot pressing and curing to obtain a thermally conductive insulating material.

[0011] It is further defined that the mass ratio of tris(hydroxymethyl)aminomethane, PDA and ND in S1 is 2:1:10.

[0012] It is further defined that the preparation process of the tris(hydroxymethyl)aminomethane solution in S1 is: after mixing tris(hydroxymethyl)aminomethane and deionized water in a mass volume ratio of 2g:1L, the pH value is adjusted to 8.5 using dilute hydrochloric acid.

[0013] It is further defined that the average particle size of ND in S1 is 1 μm.

[0014] It is further defined that the freeze-drying process in S1 is: cooling to -35°C at a rate of 5°C / min, keeping warm for 2.5 hours, evacuating to 999Pa, and then entering a total of 16 freezing processes, of which the first stage is keeping warm at -35°C for 2 hours, the second stage is keeping warm at -30°C for 2 hours, and so on until the 16th stage is keeping warm at 35°C for 2 hours.

[0015] It is further defined that the mass volume ratio of PDA-ND, acetone and tridecafluorooctyltrimethoxysilane in S2 is 1 g:125 mL:1 g.

[0016] It is further defined that the freeze-drying process in S2 is: cooling to -35°C at a rate of 5°C / min, keeping warm for 2.5 hours, evacuating to 999Pa, and then entering a total of 16 freezing processes, of which the first stage is keeping warm at -35°C for 2 hours, the second stage is keeping warm at -30°C for 2 hours, and so on until the 16th stage is keeping warm at 35°C for 2 hours.

[0017] It is further defined that the mass ratio of F-ND, curing agent and epoxy resin in S3 is 36.25:45:100.

[0018] It is further defined that the hot pressing curing process in S3 is: keeping the temperature at 150°C for 2 hours under a pressure of 15 MPa, and then heating to 180°C and keeping the temperature for 2 hours.

[0019] A second object of the present invention is to provide a thermally conductive packaging insulating material prepared by the above method.

[0020] A third object of the present invention is to provide an application of the above-mentioned thermally conductive packaging insulating material, specifically as a potting material for electronic devices.

[0021] Beneficial effects:

[0022] The present invention first uses diamond powder coated with dopamine hydrochloride, and then obtains fluorinated diamond powder F-ND coated with perfluorosilane by polymerization reaction between tridecafluorooctyltrimethoxysilane and dopamine chains on the surface of diamond, and then adds the diamond powder F-ND as a filling phase into the epoxy resin matrix, thereby improving the thermal conductivity of the epoxy resin composite material. Compared with the prior art, the present invention has at least the following advantages:

[0023] (1) The present invention adopts the method of surface modification functional groups to graft macromolecular functions on the surface of ND fillers, and improves the phenomenon of strong unilateral precipitation effect and poor dispersion of diamond in epoxy resin polymer composite materials through chemical bond forces, thereby improving the dispersion degree between filler particles, reducing the impact of unilateral sedimentation, and improving the thermal conductivity and insulation properties of the composite materials.

[0024] (2) The composite material prepared by the present invention has a thermal conductivity of 0.48 W / m·K at 25°C when the content of F-ND is 20 wt%. This is more than twice that of pure epoxy resin (0.2 W / m·K). At the same time, the material also maintains a relatively high level in terms of DC resistivity and DC breakdown field strength.

[0025] (3) The preparation method of the thermally conductive packaging insulating material provided by the present invention is simple, the preparation process cost is low, the repeatability is high, the implementation is easy, the stability is good, the environmental protection is good, and the operation of the required instruments is simple and safe, which provides an effective way to solve the problem of poor thermal conductivity of epoxy resin-based potting glue used for electronic device packaging. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a comparison chart of Fourier transform infrared spectra of PDA-ND and F-ND prepared in Example 1, ND-F and ND prepared in Comparative Example 1;

[0027] Figure 2 It is a comparison chart of the thermal gravimetric curves of PDA-ND and F-ND prepared in Example 1, and ND-F and ND prepared in Comparative Example 1;

[0028] Figure 3 X-ray diffraction patterns of EP, ND / EP, PDA-ND / EP, F-ND / EP, and ND-F / EP composite materials prepared for different embodiments and comparative examples;

[0029] Figure 4 This is a cross-sectional scanning electron microscope image of the EP composite material prepared in Comparative Example 3;

[0030] Figure 5 This is a cross-sectional scanning electron microscope image of the ND / EP composite material prepared in Comparative Example 2;

[0031] Figure 6 This is a cross-sectional scanning electron microscope image of the PDA-ND / EP composite material prepared in Comparative Example 1;

[0032] Figure 7 This is a cross-sectional scanning electron microscope image of the F-ND / EP composite material prepared in Example 1;

[0033] Figure 8 This is a cross-sectional scanning electron microscope image of the ND-F / EP composite material prepared in Comparative Example 4;

[0034] Fig. 9 The thermal conductivity and improvement rate bar graphs of the EP, ND / EP, PDA-ND / EP, and F-ND / EP composite materials prepared in Example 1 and different comparative examples;

[0035] Fig.10 The volume resistivity bar graphs of EP, ND / EP, PDA-ND / EP, F-ND / EP, and ND-F / EP composite materials prepared in Example 1 and different comparative examples are shown;

[0036] Fig.11 Weibull distribution diagram of the DC breakdown field strength of EP, ND / EP, PDA-ND / EP, F-ND / EP, and ND-F / EP composite materials prepared in Example 1 and different comparative examples. DETAILED DESCRIPTION

[0037] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0038] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0039] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0040] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art, and the purity of the solid and liquid reagents used is analytically pure.

[0041] The epoxy resin used in the following examples and comparative examples is AG-70 epoxy resin, and the curing agent is DDS.

[0042] Example 1

[0043] The method for preparing a high thermal conductivity epoxy resin composite material in this embodiment comprises the following steps:

[0044] Step 1, add tris(hydroxymethylaminomethane) Tris into a beaker containing deionized water and stir, adjust the pH to 8.5 with HCl solution, add PDA and ND to the solution, stir for 12 hours to obtain a mixed suspension, then centrifuge the suspension to discard the supernatant, and wash the precipitate obtained after centrifugation with deionized water to obtain a washed suspension;

[0045] Specifically, the average particle size of ND was 1 μm, Tris and deionized water were 2 g and 1 L, the mass ratio of PDA, ND and Tris was 1:10:2, the speed of the magnetic stirrer was 500 r / min, the speed of the centrifuge was 700 r / min, and the working time was 5 min.

[0046] Step 2, the washed suspension is treated with a freeze dryer to obtain dry ND powder wrapped with PDA polymer chains, referred to as PDA-ND, for later use;

[0047] The specific freeze-drying process is: cooling to -35°C at a rate of 5°C / min, keeping warm for 2.5 hours, evacuating to 999Pa, and then entering a total of 16 freezing processes. The first stage is keeping warm at -35°C for 2 hours, the second stage is keeping warm at -30°C for 2 hours, and so on until the 16th stage is keeping warm at 35°C for 2 hours, and the process ends.

[0048] Step 3, adding the PDA-ND obtained in step 2 into a three-necked beaker containing acetone solution and stirring, adding tridecafluorooctyltrimethoxysilane while stirring, centrifuging the obtained suspension after stirring, discarding the supernatant, and washing the obtained precipitate with alcohol and deionized water in sequence to obtain a washed suspension;

[0049] Specifically, the mass ratio of tridecafluorooctyltrimethoxysilane to PDA-ND is 1:1, and the ratio of acetone solution to PDA-ND is 125 mL:1 g.

[0050] Step 4, treating the washed suspension obtained in step 3 with a freeze dryer to obtain dry ND powder grafted with tridecafluorooctyltrimethoxysilane, referred to as F-ND;

[0051] The specific freeze-drying process is: cooling to -35°C at a rate of 5°C / min, keeping warm for 2.5 hours, evacuating to 999Pa, and then entering a total of 16 freezing processes. The first stage is keeping warm at -35°C for 2 hours, the second stage is keeping warm at -30°C for 2 hours, and so on until the 16th stage is keeping warm at 35°C for 2 hours, and the process ends.

[0052] Step 5, adding F-ND and DDS curing agent (4,4'-diaminodiphenyl sulfone) into AG-70 epoxy resin, heating and stirring, and using vulcanization hot pressing and hot pressing curing to prepare a 20wt% F-ND / EP composite material, named F-ND / EP.

[0053] The specific mass ratio of epoxy resin, curing agent and F-ND is 100:45:36.25, and the curing process is 150° C. for 2 h, then 180° C. for 2 h, and the pressure is 15 MPa.

[0054] Comparative Example 1

[0055] The difference between this comparative example and Example 1 is that after step 2, PDA-ND is used to directly replace F-ND in step 5 to prepare the epoxy resin composite material, and the remaining process steps and parameter settings are the same as those in Example 1, and a 20wt% PDA-ND / EP composite material is prepared, which is named PDA-ND / EP.

[0056] Comparative Example 2

[0057] The difference between this comparative example and Example 1 is that the original ND is directly used instead of the F-ND in step 5 to prepare the epoxy resin composite material, and the remaining process steps and parameter settings are the same as those in Example 1, and a 20wt% ND / EP composite material is prepared, named ND / EP.

[0058] Comparative Example 3

[0059] The DDS curing agent was added into the AG-70 epoxy resin, heated and stirred, and then vulcanized, hot pressed and hot pressed to cure to prepare an EP composite material, which was named EP.

[0060] The specific mass ratio of epoxy resin to curing agent is 100:45, and the curing process is 150° C. for 2 h, then 180° C. for 2 h, and the pressure is 15 MPa.

[0061] Comparative Example 4

[0062] The difference between this comparative example and Example 1 is that steps 1 to 2 are not performed, ND powder is used instead of PDA-ND powder in step 3 to prepare the epoxy resin composite material, and the remaining process steps and parameter settings are the same as those in Example 1. The prepared composite material is named ND-F / EP.

[0063] The specific operation process is as follows:

[0064] Step 1, adding ND into a three-necked beaker filled with acetone solution and stirring, adding tridecafluorooctyltrimethoxysilane while stirring, centrifuging the obtained suspension after stirring, discarding the supernatant, and washing the obtained precipitate with alcohol and deionized water in sequence to obtain a washed suspension;

[0065] Specifically, the mass ratio of tridecafluorooctyltrimethoxysilane to ND is 1:1, and the ratio of acetone solution to ND is 125 mL:1 g.

[0066] Step 4, treating the washed suspension obtained in step 3 with a freeze dryer to obtain a dry powder, referred to as ND-F;

[0067] The specific freeze-drying process is: cooling to -35°C at a rate of 5°C / min, keeping warm for 2.5 hours, evacuating to 999Pa, and then entering a total of 16 freezing processes. The first stage is keeping warm at -35°C for 2 hours, the second stage is keeping warm at -30°C for 2 hours, and so on until the 16th stage is keeping warm at 35°C for 2 hours, and the process ends.

[0068] Step 5, adding ND-F and DDS curing agent into AG-70 epoxy resin, heating and stirring, and using vulcanization hot pressing and hot pressing curing to prepare a 20wt% ND-F / EP composite material, named ND-F / EP.

[0069] The specific mass ratio of epoxy resin, curing agent and ND-F is 100:45:36.25, and the curing process is 150° C. for 2 h, then 180° C. for 2 h, and the pressure is 15 MPa.

[0070] Effect example

[0071] The ND, PDA-ND, F-ND, ND-F, EP, ND / EP, PDA-ND / EP, F-ND / EP, and ND-F / EP prepared in the above examples and different comparative examples were subjected to structural characterization and performance test comparison, and the results are as follows:

[0072] (1) The obtained ND, PDA-ND, F-ND, and ND-F were characterized by Fourier transform infrared spectroscopy. The results are as follows Figure 1 As shown by Figure 1 It can be seen that PDA-ND is at 1532cm -1 There is a C=C skeleton vibration absorption peak at 1284cm -1 The CN stretching vibration absorption peak is at 979cm -1 The peak of aromatic CH deformation vibration is at 1146cm -1 The Si-O stretching vibration absorption peak is 1242 cm -1 The CF stretching vibration absorption peak is at 3430cm; ND, PDA-ND, and F-ND are at 3430cm -1 There are different intensities of hydroxyl stretching vibration absorption peaks everywhere, proving that the ND surface grafting is successful. However, the hydroxyl peak intensity of ND-F is not significantly weakened, indicating that the surface modification success rate of ND directly reacting with tridecafluorooctyltrimethoxysilane is very low.

[0073] (2) The obtained ND, PDA-ND, F-ND, and ND-F powders were subjected to thermogravimetric tests. The results are as follows Figure 2 As shown by Figure 2 It can be seen that when the temperature rises to 800℃, the mass of ND remains 92%, while that of PDA-ND and F-ND remains 88.2% and 86.1% respectively, indicating that there are easily oxidized functional groups on the surfaces of PDA-ND and F-ND, proving that the grafting is successful; the mass of ND-F remains 91.8%, indicating that a part of the hydroxyl groups on the surface of ND react with the tridecafluorosilane functional groups.

[0074] (3) The X-ray diffraction patterns of the obtained EP, ND / EP, PDA-ND / EP, F-ND / EP, and ND-F / EP composites are shown in Figure 2. Figure 3 As shown by Figure 3It can be seen that the characteristic diffraction peaks of ND appear at 2θ=43.95° and 75.34°, which correspond to the (111) and (110) crystal planes of ND, respectively, and correspond to the standard card (01-073-2095). Since EP belongs to the amorphous state, its characteristic diffraction peak is "bun-shaped" and appears near 2θ=10°-20°. The characteristic diffraction peaks of ND appear in ND / EP, PDA-ND / EP, F-ND / EP, and ND-F / EP composite materials. At the same time, there are no other impurity peaks in the composite materials except the characteristic diffraction peaks of ND and EP, indicating that the surface modification functional groups have not changed the crystal structure of ND. The preparation of ND / EP, PDA-ND / EP, F-ND / EP, and ND-F / EP composite materials is physical doping, and no other substances are generated.

[0075] (4) The scanning electron microscopy images of the obtained EP, ND / EP, PDA-ND / EP, F-ND / EP, and ND-F / EP composite materials are shown in Figure 2. Figure 4 , 5 , 6, 7, and 8, Figure 4 , 5 6, it can be seen that ND and PDA-ND have obvious unilateral precipitation in the EP composite material, which leads to the "stratification" of filler powder and EP and extremely uneven dispersion, which seriously affects the improvement of the thermal conductivity of the EP composite material by the filler powder. Figure 7 It can be seen that the unilateral precipitation of F-ND in the EP composite material has been improved and the dispersibility has been improved. Figure 8 It can be seen that the unilateral precipitation of ND-F in the EP composite material is slightly improved compared with ND and PDA-ND, but the effect is not as good as that of F-ND.

[0076] (5) The thermal conductivity of the obtained EP, ND / EP, PDA-ND / EP, F-ND / EP, and ND-F / EP composite materials was tested. The results are as follows Fig. 9 As shown by Fig. 9 It can be seen that when F-ND accounts for 20wt% of the composite material, the thermal conductivity of the F-ND / EP composite material is 0.48W / m·K, which is the highest thermal conductivity among all composite materials. Although the thermal conductivity of ND-F / EP is higher than that of PDA-ND / EP, it is still lower than that of F-ND / EP.

[0077] (6) The volume resistivity of the obtained EP, ND / EP, PDA-ND / EP, F-ND / EP, and ND-F / EP composites was characterized. The resistivity of different components was Fig.10 As shown, it can be seen that the conductivity of F-ND / EP decreases the least and is closest to the level of EP. The results show that the F-ND / EP composite material prepared by the method provided by the present invention still has a certain insulation level.

[0078] (7) The DC breakdown field strength of the obtained EP, ND / EP, PDA-ND / EP, F-ND / EP, and ND-F / EP composite materials was tested. The DC breakdown voltage of different components was Fig.11 As shown, it can be seen that the DC breakdown of F-ND / EP decreases the least, which is closest to the level of EP. The results show that the F-ND / EP composite material prepared by the method provided by the present invention still has a certain insulation level.

[0079] Although the present invention has been disclosed as above in the preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A method for preparing a thermally conductive insulating material, characterized in that: include: S1, adding PDA and ND to a tris(hydroxymethyl)aminomethane solution, stirring to obtain a suspension, then centrifuging, discarding the supernatant, washing the obtained precipitate with deionized water to obtain a neutral suspension, and freeze-drying the neutral suspension to obtain PDA-coated ND powder, named PDA-ND; The average particle size of NDs in S1 was 1 μm; S2, adding the PDA-ND obtained in S1 to acetone, stirring evenly, adding tridecafluorooctyltrimethoxysilane to obtain a suspension, then centrifuging, discarding the supernatant, washing the obtained precipitate with ethanol and deionized water in sequence to prepare a suspension, freeze-drying the suspension to obtain tridecafluorooctyltrimethoxysilane-modified ND powder, named F-ND; S3, mixing the F-ND obtained in S2, a curing agent and an epoxy resin, heating and stirring, and hot pressing and curing to obtain a thermally conductive insulating material; The mass ratio of F-ND, curing agent and epoxy resin in S3 is 36.25:45:

100.

2. The preparation method according to claim 1, characterized in that: The mass ratio of tris(hydroxymethyl)aminomethane, PDA and ND in S1 is 2:1:

10.

3. The preparation method according to claim 1, characterized in that: The preparation process of the tris(hydroxymethyl)aminomethane solution in S1 is as follows: after mixing tris(hydroxymethyl)aminomethane and deionized water in a mass volume ratio of 2 g:1 L, the pH value is adjusted to 8.5 using dilute hydrochloric acid.

4. The preparation method according to claim 1, characterized in that: The freeze-drying process in S1 and S2 is: cooling to -35°C at a rate of 5°C / min, keeping warm for 2.5 hours, evacuating to 999Pa, and then entering a total of 15 freezing processes, of which the first stage is keeping warm at -35°C for 2 hours, the second stage is keeping warm at -30°C for 2 hours, and so on until the 15th stage is keeping warm at 35°C for 2 hours.

5. The preparation method according to claim 1, characterized in that: The mass volume ratio of PDA-ND, acetone and tridecafluorooctyltrimethoxysilane in S2 is 1 g:125 mL:1 g.

6. The preparation method according to claim 1, characterized in that: The hot pressing curing process in S3 is: keep the temperature at 150°C for 2 hours under a pressure of 15 MPa, and then increase the temperature to 180°C and keep the temperature for 2 hours.

7. A thermally conductive insulating material prepared by the method according to any one of claims 1 to 6.

8. An application of the thermally conductive insulating material according to claim 7, characterized in that: Used as potting material for electronic devices.

Citation Information

Patent Citations

  • High-thermal-conductivity epoxy composite material and preparation method thereof

    CN110903608A

  • Three-dimensional framework material, electronic packaging adhesive and preparation method and application thereof

    CN116042132A